2017
DOI: 10.1186/s40560-017-0238-8
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of plasminogen activator inhibitor-1 as a predictive marker of mortality in sepsis

Abstract: BackgroundSepsis is one of the most significant causes of mortality in intensive care units. It indicates crosstalk between inflammation and coagulation. In this study, we aimed to identify prognostic markers among sepsis biomarkers and coagulation/fibrinolysis markers.MethodsPatients with sepsis according to the Sepsis-3 criteria were enrolled from January 2013 to September 2015. Univariate and multivariate logistic regression analyses were performed to identify an independent predictive marker of 28-day mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 28 publications
5
39
0
Order By: Relevance
“…TF expressed on various cells or released from injured cells initiates the physiologically most important TF (extrinsic) pathway, whereas PAI-1 is known to be a strong inhibitor of the fibrinolytic system. PAI-1-mediated fibrinolysis shutdown has already been described in a pig model of endotoxin-induced DIC [33] as well as in human sepsis [36]. We were able to support these findings within the presented investigation.…”
Section: Discussionsupporting
confidence: 85%
“…TF expressed on various cells or released from injured cells initiates the physiologically most important TF (extrinsic) pathway, whereas PAI-1 is known to be a strong inhibitor of the fibrinolytic system. PAI-1-mediated fibrinolysis shutdown has already been described in a pig model of endotoxin-induced DIC [33] as well as in human sepsis [36]. We were able to support these findings within the presented investigation.…”
Section: Discussionsupporting
confidence: 85%
“…Amongst the significant diagnostic markers for overt DIC, TAT and PAI-1 were the best predictors of 28-day mortality (AUROC, 0.77 and 0.81, respectively). Following similar reports, Hoshino et al [ 3 ] reported that the elevated levels of PAI-1 was associated with the poor outcome and the AUROC for 28-day mortality was 0.72, and the optimal cutoff level was 83 ng/mL. What were unique in their observations were firstly, only PAI-1 but no other coagulation markers such as TAT, plasmin-plasmin inhibitor complex, protein C, thrombomodulin, and soluble fibrin were associated with mortality.…”
Section: Main Bodysupporting
confidence: 55%
“…Furthermore, the over-suppression of fibrinolysis caused mainly by PAI-1 constitutes an important target for therapy in patients with sepsis and DIC [ 2 ]. In the former issue of Journal of Intensive Care , Hoshino et al [ 3 ] reported the clinical significance of measuring total PAI-1 antigen in sepsis in their retrospective observational study. Here, we introduce the accumulated knowledge with respect to this issue.…”
Section: Introductionmentioning
confidence: 99%
“…However, D-Dimer are usually high in ECMO patients [11] and prolonged coagulation times are associated with anticoagulant use. Moreover, PAI-1, plasminogen, α2-antiplasmin, which are usually abnormal in sepsisrelated DIC [12,13], were within normal ranges. Therefore, DIC was unlikely in our patient.…”
Section: Discussionmentioning
confidence: 86%